Multiplicity and Transitoriness of Chaotic Events - Montenegro Joo, Javier (2014)
Commonly authors of literature dealing with chaos report a single and truncated chaotic event occurring in the chaotic system they have investigated. This paper reports a multiplicity of chaotic events detected in the non-linear damped and forced oscillator. In order to detect chaos in this oscillator, a Virtual Lab (integrated and interactive computer program) was developed by the author of this report. With this Virtual Lab many chaos simulations were executed and the resulting Poincaré Maps for angles of 0° and 180° were extracted and filtered to avoid event duplicity. It has been found that chaotic events do not last forever; they have a beginning and an end, which means they are transitory. No numerical connection has been detected between the natural frequency of a chaotic oscillator with that of the periodical applied force.